(untitled) (Proceedings of Faculty of Civil Engineering, 2021)
The residential building with a basement, built back in 1955 at the address Istarska ulica 29, is of great significance for the architectural and urban history of the city of Rijeka. Namely, this building was constructed following the project commissioned by the Shipyard “3. maj” to continue the construction of the workers’ housing project “Zamet”. However, only two buildings of reduced dimensions will be constructed on the mentioned location, while the original project will be realized only at the stated location in Kantrida. Furthermore, architectural design is the hitherto unknown work of the Zagreb architect Hinko Vichra, one of only nineteen Croatian architects who graduated the School of Architecture, which was led by Drago Ibler from 1926 to 1943 as part of the Zagreb Academy of Fine Arts. Therefore, a justified interest in Vichra’s project and work is quite understandable because not much is known about it. Finally, there is an interesting project approach which connects the traditional way of building of the basement with the technology of prefabrication, predicting mounting of the skeletal system “Izolit”. This system was the forerunner of industrialized construction systems that will be developed by the company “Jugomont” from 1955 onwards and which will culminate in the development and application of the JU-61 prefab system not only in Croatia but also all over former SFR Yugoslavia. Given the extremely small number of preserved buildings from this period, which were constructed in the described way, the structure found in Rijeka deserves at least a documentation and a review.